2016
DOI: 10.15825/1995-1191-2016-3-68-73
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Disk Pump for Mechanical Circulatory Support in Cardiac Surgery (Review)

Abstract: 1 Новосибирский научно-исследовательский институт патологии кровообращения имени академика Е.Н. Мешалкина Минздрава России, Новосибирск, Российская Федерация 2 Институт теоретической и прикладной механики им. С.А. Христиановича СО РАН, Новосибирск, Российская Федерация Актуальность использования систем вспомогательного кровообращения в лечении хронической сердеч-ной недостаточности постоянно возрастает, поскольку 20% пациентов из листа ожидания ежегодно поги-бают, не дождавшись донорского сердца. Несмотря на о… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Chernyavskiy, A.M. [96,97] pointed out that one of the new research directions was the viscous friction disc pump for liquid transportation based on the Tesla pump principle, put forward the shortcomings of the current research based on the published data, and introduced the current model of disc pump. The test results showed that the pressure characteristics of the disc pump could provide necessary blood circulation parameters.…”
Section: Efficiency = 40%mentioning
confidence: 99%
“…Chernyavskiy, A.M. [96,97] pointed out that one of the new research directions was the viscous friction disc pump for liquid transportation based on the Tesla pump principle, put forward the shortcomings of the current research based on the published data, and introduced the current model of disc pump. The test results showed that the pressure characteristics of the disc pump could provide necessary blood circulation parameters.…”
Section: Efficiency = 40%mentioning
confidence: 99%
“…The studies of hemolysis in rotary pumps of ABCS showed that the greatest damage to the blood is observed in centrifugal pumps [1]. At the same time, the authors point out that the damage is mechanical and is caused by direct contact between the blood elements and the pump rotor due to the lack of boundary layers in the rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the development of Artificial Blood Circulation System (ABCS), the problem of mechanical haemolysis in the ABCS appeared [1], particularly, in their rotary pumps: axial, centrifugal and disk-shaped ones, see Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…According to their parameters: blood volume flow 3...6 liter per minute and the size of the impeller, these pumps are classified as low-flow, small-sized centrifugal pumps [6][7][8][9]. As a rule, their impeller does not contain a sleeve protruding from the impeller inlet, as is seen in industrial pumps.…”
Section: Introductionmentioning
confidence: 99%